2017
DOI: 10.1002/slct.201700973
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis, Crystal Structure, and Visible-Region Photocatalytic Activity of BaBi2 O6

Abstract: The pentavalent bismuthate BaBi 2 O 6 was prepared by a lowtemperature hydrothermal reaction using NaBiO 3 .nH 2 O and Ba (OH) 2 .8H 2 O as starting materials. The X-ray powder diffraction pattern was indexed with a hexagonal cell (space group: P-31 m), the same as a PbSb 2 O 6 -type crystal. The crystal structure of this compound was refined using synchrotron X-ray powder diffraction data. The cell parameters were found to be a = 5.57534(6) and c = 5.7381(1) Å and the final reliability (R) factors obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 19 publications
4
25
0
Order By: Relevance
“…These amounts are larger than those for the products using nitrate solution. The lattice parameters of the Co-, Ni-and Cu phases were a = 3.8888(8), c = 7.357(1) ¡, a = 3.8876 (7), c = 7.360(1) ¡ and a = 3.8960 (7), c = 7.368(2) ¡, respectively. From these results, the products are thought to be isostructural with BiOCl, with a small amount of transition-metals incorporated to the only metal site in BiOCl.…”
Section: Hydrothermal Reaction With Nitrate Solutionsmentioning
confidence: 99%
“…These amounts are larger than those for the products using nitrate solution. The lattice parameters of the Co-, Ni-and Cu phases were a = 3.8888(8), c = 7.357(1) ¡, a = 3.8876 (7), c = 7.360(1) ¡ and a = 3.8960 (7), c = 7.368(2) ¡, respectively. From these results, the products are thought to be isostructural with BiOCl, with a small amount of transition-metals incorporated to the only metal site in BiOCl.…”
Section: Hydrothermal Reaction With Nitrate Solutionsmentioning
confidence: 99%
“…14 Experimentally, a low-temperature hydrothermal environment of B120 1C was found to be ideal for preparing bismuth oxides with Bi 5+ and mixed Bi 5+ /Bi 3+ ions from NaBiO 3 ÁnH 2 O. [15][16][17][18][19][20] This method has been proven to be efficient for synthesizing new inorganic materials [21][22][23][24][25][26][27][28][29][30] and the striking characteristic of it is to produce Bi 5+ , as evidenced by previously synthesized bismuth oxides. 13,[15][16][17][18][19]29,31,32 In addition, the perovskite-type Ba(Bi 0.75 M 0.25 )O 3 (M = Li, Na) and Ba(Bi 0.67 M 0.33 )O 3 (M = Mg, Ca, Sr, Ba, Cd, Cu) were synthesized under high oxygen pressure, which also exhibited Bi 5+ at the B-site.…”
Section: Introductionmentioning
confidence: 99%
“…14) However, a highly crystalline BaBi 2 O 6 was obtained using a barium hydroxide solution at 120°C. 13) These results suggested that the room-temperature reaction in barium chloride solution was an ion exchange one, 14) whereas the reaction in barium hydroxide solution at 120°C was a dissolutionrecrystallization process. 13) On the other hand, the hydrothermal reaction in strontium nitrate solution at 180°C produced pyrochlore-type (Sr 0.52 Bi 0.4 ) 2 Bi 2 O 6.58 (CO 3 ) 0.14 ; 2) however, the hydrothermal reaction in strontium hydroxide solution at 80°C yielded pyrochlore-type Sr 2 Bi 2 O 7 .…”
mentioning
confidence: 97%
“…13) These results suggested that the room-temperature reaction in barium chloride solution was an ion exchange one, 14) whereas the reaction in barium hydroxide solution at 120°C was a dissolutionrecrystallization process. 13) On the other hand, the hydrothermal reaction in strontium nitrate solution at 180°C produced pyrochlore-type (Sr 0.52 Bi 0.4 ) 2 Bi 2 O 6.58 (CO 3 ) 0.14 ; 2) however, the hydrothermal reaction in strontium hydroxide solution at 80°C yielded pyrochlore-type Sr 2 Bi 2 O 7 . 1) The different crystal phases were attributed to the different reaction temperature and pH of the solutions, which influence on Bi valence ratio and/or crystal growth speed of the product.…”
mentioning
confidence: 97%
See 1 more Smart Citation